IMPLEMENTASI LKPD DENGAN PENDEKATAN RME BERBASIS ETNOMATEMATIKA “GEDRIK” MATERI LUAS BANGUN DATAR - Wiryanto, Wiryanto; Franstito, Nadiva Ade; Rahmawati, Ika (TRANSFORMASI, 2024)
This research aims to determine the effectiveness of student worksheets that use the RME approach based on the ethnomathematics of gedrik game in the mathematics learning process regarding the area of flat shapes. This research allows students to carry out learning activities from contextual situations based on the traditional gedrik game, which is developed into cutting, measuring, calculating, and comparing activities. The method used is descriptive qualitative with a design research type in three stages, namely: preparation, experimental implementation, and retrospective analysis. This research involved five grade 5 students of SDN 1 Ngantru as respondents. The results of the research show that there is a compatibility between the Actual Learning Trajectory and the Hypothetical Learning Trajectory, meaning that the student worksheets with the RME approach based on ethnomathematics of gedrik game is effectively used in understanding students about the area of flat shapes. The results of this research can be tested in other schools at the same level, and developed by utilizing other cultures that are close to students’ daily lives in the form of student worksheets with an ethnomathematics-based RME approach